2014
DOI: 10.1001/jamasurg.2013.4830
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Comparison of Standardized Online Surgical Curricula for Use in Low- and Middle-Income Countries

Abstract: IMPORTANCE Surgical conditions are an important component of global disease burden, due in part to critical shortages of adequately trained surgical providers in low-and middle-income countries.OBJECTIVES To assess the use of Internet-based educational platforms as a feasible approach to augmenting the education and training of surgical providers in these settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Twenty-five (13.7%) studies reported limitations to telemedicine for surgical care in LMICs. These included Internet bandwidth, network instability and coverage [ 69 , 78 , 82 , 122 124 ], high costs of technology set-up [ 55 , 125 ], and safety, privacy and confidentiality concerns [ 117 , 118 , 126 ]. Poor image quality for asynchronous (where information transmission and response do not take place in real-time) telemedicine [ 127 ], inability to confirm delivery of information by SMS recipients [ 128 , 129 ], and time zone differences for international collaborations and mentoring [ 31 ] were additional limitations that were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five (13.7%) studies reported limitations to telemedicine for surgical care in LMICs. These included Internet bandwidth, network instability and coverage [ 69 , 78 , 82 , 122 124 ], high costs of technology set-up [ 55 , 125 ], and safety, privacy and confidentiality concerns [ 117 , 118 , 126 ]. Poor image quality for asynchronous (where information transmission and response do not take place in real-time) telemedicine [ 127 ], inability to confirm delivery of information by SMS recipients [ 128 , 129 ], and time zone differences for international collaborations and mentoring [ 31 ] were additional limitations that were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Residents are still encouraged to register with COSECSA to allow them the benefit from additional training opportunities that are not available through UR such as the School for Surgeons 21 . Comparison between the SCORE curriculum and School for Surgeons did not find significant differences between the two platforms although one was designed for US surgical postgraduates and the other for sub-Saharan African surgical providers 22 .…”
Section: Cosecsa/asea Publication -East and Central African Journal Omentioning
confidence: 91%
“…Virtual international meetings have been held successfully prior to the pandemic in response to environmental concerns and financial limitations. 6 - 10 …”
Section: To the Editormentioning
confidence: 99%